(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Alcoholism, or alcohol use disorder, is a widespread public health problem that negatively affects both physical and mental health. This paper examines the nature of alcoholism and the harmful effects of alcohol on the human body. It discusses how excessive and long-term alcohol consumption damages major organs, including the brain, liver, heart, digestive system, and immune system. In addition, the psychological and social consequences of alcoholism, such as depression, behavioral changes, family conflicts, and reduced work performance, are highlighted. The study also emphasizes the importance of prevention, education, and treatment in reducing alcohol-related harm. Understanding the impact of alcohol on the human body can help promote healthier choices and support effective intervention strategies against alcohol addiction.